Making Digital Cultures of Gender and Sexuality With Social Media. (September 2016) - Burgess, Jean; Cassidy, Elija; Duguay, Stefanie; Light, Ben
This article introduces a special issue concerning the interweaving of gender, sexuality, and social media. There are 10 articles included in the issue which together map out a landscape of diverse areas of interest covering topics such as sexism and harassment, health and wellbeing, relationships, and leisure.